A study on the immune system of some Antarctic teleost species. - SCAPIGLIATI G; ROMANO N; BALDASSINI MR; TERRIBILI FR; MAZZINI M.; ABELLI, Luigi (Camerino University Press, 1997)
Serum Ig from four different Antarctic fish species were studied. Morphological analysis of the thymus of Trematomus bernacchiii did not evidence appreciable difference with that of other teleosts. Using a polyclonal antibody raised against sea bass Ig, cross-reactivity with H AND L chains of all species analysed was observed. An indirect ELISA was developed and detected the Ig concentrations in sera of the Antarctic species, using as standard sea bass Ig.